Clinical and laboratory profile of dengue fever in hospitalized children in a tertiary care hospital in Bangladesh (BIRDEM Medical Journal, 2020)
Background: Dengue is a major health problem affecting Bangladesh. The number of cases have increased over the last few years with a large number of population being children. However data regarding dengue among children is limited. The objectives of this study were to see the clinical and laboratory profile of dengue fever (DF) in children and their outcome.Methods: This cross - sectional study was carried out in the department of Paediatrics, BIRDEM General Hospital 2 from June 2018 to August 2019. Three hundred and ten confirmed dengue cases were enrolled in the study. Their clinical profile and laboratory findings including haemoglobin (Hb%), haematocrit (Hct), total count of white blood cells (TC), differential count of white blood cells ( DC), platelet count (PC), serum alanine aminotransferase ( S. ALT), serum aspartate aminotransaminase (S. AST), prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (APTT) were documented. Comparison was made between the clinical and laboratory profile with severity of dengue.Results: One hundred and ninety eight (63.9%) had dengue fever, 58(18.7%) had dengue haemorrhagic fever (DHF I, II) and 54 ( 17.4 %) had dengue shock syndrome ( DHF III and IV). All the patients had fever, vomiting was present in 40%, ascites and skin rash in 21 %, pleural effusion 20%, abdominal pain 14% and 12.2% came with shock.Thrombocytopenia, raised hct, raised liver enzymes and abnormal coagulation profile were more common in dengue haemorrhagic fever when compared to patients with dengue fever.Conclusion: Gastrointestinal features like vomiting, ascites ,abdonminal pain were common presentations. Thrombocytopenia, raised hct, raised liver enzymes, abnormal coagulation profile were more common in dengue haemorrhagic fever.Birdem Med J 2020; 10(3): 200-203